Characterisation and stability study of 3 natural oil creams prepared by a commercial emulsifier (gellinov®) using cold mixing technique - Ali, Ros Azliani (2016)
Cosmetics such as cream are semi solid type preparation products. Preparation of cream through conventional method and hot method is quite tedious and time consuming, plus it still difficult to characterize and required specific flow properties to be stable. Creams from three components, thickening emulsifier, purified water, and oil were prepared using cold method. Each batch consists of 13 samples with different concentrations. A total of 39 cream formulation were generated from Design Expert 10 (DXI 0) software. The natural oils used were jojoba oil, olive oil and virgin coconut oil incorporation with thickening emulsifier, Gellinov®. The effect of the two independent variables on the response variables was studied by response surface plots and contour plots generated by the Design-Expert software. All the three different natural oil showed similarity in profile and stable when loaded with Gellinov®. As conclusion, the cream formulation produced using scientific design experiments with practicing cold method technique were faster and met the good physical properties and stability of cream for three different natural oils.